Philosophy of Mathematics in Primary Education Mathematics Learning: Ontological, Epistemological, and Methodological - Fajri, Hardian Mei; Raihan, Muhammad Dawam; Sumantri, Mohamad Syarif; Nurhasanah, Nina; Utomo, Erry (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
The purpose of this study is to examine the relationship, position, and role of the philosophy of mathematics in learning mathematics in basic education through the perspective of the scope of philosophy, namely ontological mathematics, epistemological mathematics, and methodological mathematics. This research is a qualitative descriptive research with a literature study approach. Data collection techniques are carried out through the documentation method of articles originating from the Google Scholar database, as well as books related to the philosophy of mathematics. Data analysis techniques consist of data reduction, data presentation, and conclusion. The results highlight three main aspects within the scope of the philosophy of mathematics: ontological, epistemological, and methodological. Ontological mathematics addresses the ontological foundations of mathematics for teaching, including the role of mathematics in various contexts. The epistemology of mathematics emphasizes the importance of understanding the discipline from multiple perspectives to enhance learning and curriculum design. Meanwhile, the methodology of mathematics highlights the role of specific methods in determining mathematical solutions. In conclusion, understanding the philosophy of mathematics in these three aspects is important for educators to improve the learning process of mathematics at the primary level comprehensively and optimally.